Mobile Payment Adoption in Pakistan: Extending UTAUT with Islamic Religiosity (Journal of Social Sciences Review, 2023)
In recent years, mobile payments have increased around the world. However, limited studies have examined m-payment users' intentions and behaviors. Using the UTAUT framework, this study addresses this research gap by exploring the primary factors that influence users' behavior and intention toward mobile payments. An empirical cross-sectional survey was conducted in order to achieve the study's objectives. Three hundred and twenty-four samples from Pakistan were used to test the proposed conceptual model. The results indicate that performance expectation, social influence, effort expectation, and facilitating conditions are critical to predicting m-payment usage and behavior. There is also an association between Islamic religiosity and behavioral intentions.
Keywords: Mobile Payment; UTAUT; Behavioral Intention; Use Behaviour; Religiosity